PENDEKATAN KAIZEN DALAMPERBAIKAN MUTU PENDIDIKAN - Roofi`'i, Mohammad (Al Ulya: Jurnal Pendidikan Islam, 2022)
This study aims to develop a quality improvement system that can be used by various agencies, especially educational institutions. The kaizen approach in social culture is very suitable to be applied in Indonesia, because kaizen must be implemented by all sectors through cooperation and it is in accordance with the principle of mutual cooperation that we have. especially in this day and age the quality of education has become a very important thing to improve. This of course requires the support and participation of all relevant parties